Analysis of Waste Separation Drivers in Urban Centers Using the Theory of Planned Behavior and the Norm Activation Model - Maghfiroh, Meilinda Fitriani Nur; Muqimuddin, Muqimuddin; Sartika, Widya; Redi, Anak Agung Ngurah Perwira; Abdallah, Bayu Nur; Hutahaean, Glenardo Antoi; Apriani, Ratna Agil (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2024)
Urban centers worldwide are grappling with complex waste management challenges, including efficient collection, transportation, processing, and an over-reliance on landfills. A promising approach to mitigate these issues lies in bolstering public participation in waste separation, which could significantly improve recycling efforts. To effectively encourage this practice, it is crucial to understand the underlying factors that motivate community engagement in waste segregation activities. This study utilizes the Theory of Planned Behavior and the Norm Activation Model to identify and analyze determinants influencing individuals' propensity to separate waste in the sampling area of Balikpapan City, Indonesia. Balikpapan, one of the cities in Indonesia, is currently facing several distinct challenges related to waste management. Through the empirical validation of eight hypotheses, it becomes apparent that the presence of market facilitators (H3) and the influence of past behavior (H5) play pivotal roles in shaping the intention to engage in waste separation. The findings suggest that providing accessible, well-maintained market facilities and initiatives designed to enrich the public's waste separation experience are essential strategies. Implementing these strategies could significantly improve waste separation practices within specific urban contexts such as Balikpapan, Indonesia, and other cities facing similar environmental management challenges.